2022
DOI: 10.7554/elife.72867
|View full text |Cite
|
Sign up to set email alerts
|

Type I and II PRMTs inversely regulate post-transcriptional intron detention through Sm and CHTOP methylation

Abstract: Protein arginine methyltransferases (PRMTs) are required for the regulation of RNA processing factors. Type I PRMT enzymes catalyze mono- and asymmetric dimethylation; Type II enzymes catalyze mono- and symmetric dimethylation. To understand the specific mechanisms of PRMT activity in splicing regulation, we inhibited Type I and II PRMTs and probed their transcriptomic consequences. Using the newly developed Splicing Kinetics and Transcript Elongation Rates by Sequencing (SKaTER-seq) method, analysis of co-tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 80 publications
1
12
0
Order By: Relevance
“…3 e). Collectively, although we cannot exclude possible posttranscriptional conversion of V1 to V2 upon DRB treatment, it is likely that the rapid drop in V1 levels upon DRB treatment is transcript stability-related, as DRB also inhibits kinase activity essential for the splicing process [ 35 ] and PRMT1 and PRMT5 have been reported to regulate intron retention post-transcriptionally [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 e). Collectively, although we cannot exclude possible posttranscriptional conversion of V1 to V2 upon DRB treatment, it is likely that the rapid drop in V1 levels upon DRB treatment is transcript stability-related, as DRB also inhibits kinase activity essential for the splicing process [ 35 ] and PRMT1 and PRMT5 have been reported to regulate intron retention post-transcriptionally [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…PRMT5 depletion or inhibition leads to aberrant splicing and transcriptome changes [ 7 , 8 , 10 , 32 , 33 ]. Interestingly, a recent study on PRMT5 regulated splicing mechanisms indicates a critical role for the spliceosome component SmB protein methylation by PRMT5 [ 36 ]. We found that PRMT5 inhibition or knockdown resulted in downregulation of ATF4 and downstream ATF4 regulated UPR genes.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation is a post-translational modification that functions primarily in cell signaling and cell fate decisions [ 180 , 181 , 182 , 183 ]. However, recent studies showed that methylation might also be involved in regulation of pre-mRNA splicing [ 184 , 185 , 186 , 187 , 188 , 189 ]. Methylation is executed by members of the PRMT family and the putative arginine methyltransferase NDUFAF7.…”
Section: Role Of Post-translational Modifications In Regulation Of Sp...mentioning
confidence: 99%
“…Indeed, the core spliceosome components, SmB and SmD1/3, are key PRMT5 substrates enabling the assembly of the mature core small nuclear ribonucleoproteins (snRNPs) [ 228 ]. The importance of PRMT5 for splicing has since been demonstrated by numerous approaches including genetic knockout and enzymatic inhibition [ 223 , 224 , 225 , 229 , 230 ]. More importantly, there is a growing appreciation that PRMT5 regulates splicing events that contribute to genome stability in stem cells.…”
Section: Dna Damage Repair In Cscs and Therapeutic Interventionmentioning
confidence: 99%